Workplace Bullying and It’s Impact and Remedies in the 21st Century Issues - Geleta, Negash (American International Journal of Social Science Research, 2020)
This paper is prepared to see the concept of bullying and its impacts in the work place and suggest some remedies based on the empirical data. Then the rationale of this paper document is to address why and how businesses organization should promote healthy work environments, to stimulate awareness of WPB and its negative impact on employee health, to explore current and prospective anti-WPB laws, and to present employer and employee responsive strategies to combat this business challenge. This activity was performed by using introducing the topic, reviewing the existing literature and drawing conclusion which can help different organization to update their current position.